Planejamento orientado pela água: possibilidades de reabilitação do riacho Tauape - Guedes, Joana Pimentel (2023)
The growth of cities and the consequent advance of urbanization changed “hydrosocial contract” - values and agreements (implicit or not) between communities, governments and companies on how water resources should be managed. The rivers, essential for the development of human settlements, came to be seen as an obstacle to urban expansion. The implementation of new forms of water management, with the optimization of the river for services such as sanitation and urban drainage, fragmented the natural landscape resulting in unsustainable cities, either in developed or developing countries. The supply of drinking water and access to basic sanitation in urban areas have decreased, and its maintenance and improvement are the biggest current challenges of public managers in the face of the global trend of urban population growth. Recognizing the decisive role in the preservation, protection, restoration, rehabilitation and reuse of hydrological resources that urban planning has, this dissertation is a research about the use of water resources as the structuring element of urban planning. The Tauape Creek, located in sub-basin B1 in the city of Fortaleza (CE) was used as object of study. Through the Geodesign approach and the application of information modeling tools, methods of evaluation, modification and impact verification of changes in sub-basin B1 were developed. For this, data from several different spheres were used, in order to gather the largest amount of information about the site, and bioremediation cells (BCell) were the elements used in the research as possible means of rehabilitation of the area. In the end, it was found that the use of these devices has the ability to improve environmental conditions and make the area more resilient, and the calculations used demonstrate the feasibility of a territorial planning guided by water.